(untitled) (Damu Journal of Sport Sciences, 2025)
The aim of the research was to develop educational units based on the ADDIE educational model using visual reinforcement tools and to identify the effect of ADDIE using visual reinforcement tools on students' learning of some football skills. The aim was to identify the superiority of the experimental and control groups in students' learning of some football skills. The researchers used the experimental approach because it suited the objectives and hypotheses of the research to the nature of the problem. The researchers defined the research community intentionally, consisting of 174 students from Al-Sudair Second Complementary School for Boys in the General Directorate of Education in Salah al-Din for the 2024-2025 academic year, divided into three classes. An experimental design was used for two equal, independent groups. The research sample was systematically randomly selected, comprising 30 students, 15 from Class A to represent the experimental group, and 15 from Class B to represent the control group. One of the most important findings of the research is the increased skill proficiency of students taught using the ADDIE model, as they demonstrated significant improvement in their skill performance in soccer compared to the other groups. This indicates the model's effectiveness in enhancing practical learning. One of the most important recommendations is to benefit from the application of the ADDIE model using visual reinforcement methods to maximize the educational process.